Maqasid Shariah Parameters to Re-Design Policy Performance Fintech Lending Sharia in Indonesia - Fikriawan, Suad; Ismail, Faisal Bin Husen; Mahmudah, Siti Nur; Amila, Amila (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study scrutinizes the integration of Sharia principles within Indonesia’s burgeoning fintech sector, zeroing in on the regulatory levers that shape compliance and public trust. Its academic contribution is to forge a Maqasid-al-Sharia policy framework that ties doctrinal objectives to concrete supervisory tools and technological safeguards. Drawing on in-depth interviews with regulators, platform executives, and scholars, we expose three stubborn frictions: shallow consumer literacy, fragmented oversight, and ad-hoc adoption of transparency technologies. We show how blockchain-based audit trails and tiered disclosure standards can seal these gaps while preserving Islamic ethical mandates. The evidence recasts regulators from passive gatekeepers to active market architects, offering a blueprint for rule-making that ignites Sharia-compliant innovation and shields borrowers from predatory practices.